2001
DOI: 10.1007/3-540-44566-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Time Pressure and Cognitive Load on the Basis of Speech: An Experimental Study

Abstract: Abstract.In an experimental environment, we simulated the situation of a user who gives speech input to a system while walking through an airport. The time pressure on the subjects and the requirement to navigate while speaking were manipulated orthogonally. Each of the 32 subjects generated 80 utterances, which were coded semi-automatically with respect to a wide range of features, such as filled pauses. The experiment yielded new results concerning the effects of time pressure and cognitive load on speech. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 5 publications
0
40
0
Order By: Relevance
“…Some researches Mueller et al, 2001;Jameson et al, 2006 showed that some speech features are related to a person's cognitive load levels, such as filled pauses and the number of sentence fragments, and tried to recognize cognitive load levels from a number of high level features by using Bayesian network (Mueller et al, 2001;Jameson et al, 2006). Word frequency and use of first-person plurals are also used to estimate cognitive load.…”
Section: Linguistic Feature Based Measuresmentioning
confidence: 99%
“…Some researches Mueller et al, 2001;Jameson et al, 2006 showed that some speech features are related to a person's cognitive load levels, such as filled pauses and the number of sentence fragments, and tried to recognize cognitive load levels from a number of high level features by using Bayesian network (Mueller et al, 2001;Jameson et al, 2006). Word frequency and use of first-person plurals are also used to estimate cognitive load.…”
Section: Linguistic Feature Based Measuresmentioning
confidence: 99%
“…These BNs serve as time slices for the DBN. A BN for the interpretation of speech symptoms was learned on the basis of two experiments (see Müller, Großmann-Hutter, Jameson, Rummer, & Wittig, 2001;Kiefer, 2002), while another BN for the interpretation of features of manual input behavior was constructed on the basis of a literature study (see Lindmark, 2000). The combination of these two BNs allows READY to make inferences on the basis of multimodal imput.…”
Section: Example Application Domainmentioning
confidence: 99%
“…pitch, prosody, pauses, and disfluencies, have also been found to be changing under high levels of CL [4,[8][9][10]. Such measures allow non-intrusive analysis as they are based on speech data generated by users while they complete the task.…”
Section: Introductionmentioning
confidence: 99%